Consumptivism of Gender Role in Ni Nyoman Sani’s Works of Arts - Hardiman Hardiman; I Nyoman Darma Putra; Nengah Bawa Atmadja; I Gede Mudana; Made Hery Santosa (Politeknik Negeri Bali, 2019)
All this time, a woman has often been placed as an object per se in visual art in Bali. Actually, there is an ideology behind the work of women visual artists in Bali. This article reveals and describes the gender ideology that works behind the visual representation of Ni Nyoman Sani’s works. This article concludes that the gender ideology works behind Ni Nyoman Sani’s work, that is, concerning the consumptivism of the gender role in its use. It is expected that this discussion can give us a broader and deeper understanding of the gender ideology that works behind Ni Nyoman Sani’s creative process.